Menelaah Kompetensi Pedagogik Guru Bahasa Indonesia di MTs Negeri 3 Medan dan MTs Al-Jami’yatul Washliyah Tembung - Liza Handayani Batu Bara; Ummi Nur Afinni Dwi Jayanti; Aulia Meylani; Putri Husnul Khotimah Harahap; Rodia Tammardia Siregar (Universitas Muhammadiyah Enrekang, 2023)
The research is aimed at analyzing the quality of pedagogical competences of Indonesian language teachers at the level of State MTs Negeri 3 Medan and MTs Al-Jami’yatul Washliyah Tembung. As for the research method used using a qualitative approach in the form of a descriptive investigation method by performing observations and descending directly to the field in using the interview method related to being the result of an interview with an Indonesian language teacher as the primary data and the results of the interview with the head of school as secondary data. Based on the results of the research found showed that the pedagogical competence of Indonesian language teachers at the level of MTs Negeri 3 Medan and MTs Al-Jami’yatul Washliyah Tembung is good enough only the methods used are different, because each school must have its respective roles and policies to get the best results. The pedagogical competence of teachers plays an important role in learning, because it is from here that students will obtain learning according to the good learning systematics, in addition to qualifications in terms of competence, teachers must also meet other qualifications that are academic. Teachers have a scientific educational background so they have academic and intellectual expertise.